2014 Brazilian Symposium on Software Engineering 2014
DOI: 10.1109/sbes.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Usability Inspection Technique Based on Quantitative and Qualitative Analysis

Abstract: Usability is one of the most important factors that determine the quality of software product. Many usability inspection methods are gaining popularity as an effective alternative for addressing usability issues. However, usability evaluations are often avoided by developers and software companies due to their lack of knowledge and experience in the field. Usability evaluation can be expensive in terms of time and human resources; and sometimes companies' projects do not have budget to hire an expert inspector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Valentim et al [15] and Valentim and Conte [16] describe the results of the studies. The statistical test results showed that MIT 2 obtained similar effectiveness and efficiency as the Heuristic Evaluation in both the first and the second feasibility study.…”
Section: The Observational Studymentioning
confidence: 99%
“…Valentim et al [15] and Valentim and Conte [16] describe the results of the studies. The statistical test results showed that MIT 2 obtained similar effectiveness and efficiency as the Heuristic Evaluation in both the first and the second feasibility study.…”
Section: The Observational Studymentioning
confidence: 99%
“…An inherited and transmitted software inspection problem that is remained after three decades is choosing, evaluation and appraisal of inspectors for an inspection process [7], [8]. None of the existing models focus on the selection procedures, qualification process, or even recommend a placement test of their abilities.…”
Section: Introductionmentioning
confidence: 99%
“…To identify and organize the barriers faced by OSS project newcomers, we conducted a qualitative study relying on four different sources: (i) studies gathered via a systematic literature review (SLR) that aimed at identifying and organizing the barriers evidenced by the literature (Steinmacher et al, 2014c(Steinmacher et al, , 2015c; (ii) feedback from 9 students after they contributed to OSS projects (Steinmacher et al, 2014d); (iii) 24 answers to an open question sent to 9 OSS projects (Steinmacher et al, 2014d); and, (iv) semi-structured interviews with 35 developers from 13 different projects, including newcomers, dropouts, and experienced members. To analyze the data, we used open coding and axial coding procedures of Grounded Theory (Strauss and Corbin, 2007), which are increasingly used to study the human aspects of Software Engineering (Hoda et al, 2010), for example (Smolander et al, 2008;Dagenais et al, 2010;Treude and Storey, 2010;Viana et al, 2012;Pham et al, 2013;Costa Valentim and Conte, 2014;Dittrich, 2014;França et al, 2014a).…”
Section: Chapter Barriers Faced By Newcomers To Ossmentioning
confidence: 99%